Selected issues in Islamic economics - Mukaramah Harun; Ahmad Zafarullah Abdul Jalil; Norazlina Abd Wahab (Penerbit Universiti Utara Malaysia, 2016)
[This book] is a collection of articles discussing various issues from the perspective of Islamic economics.